Study of silica templates in the rice husk and the carbon–silica nanocomposites produced from rice husk. (December 2015) - Larichev, Yu.V.; Yeletsky, P.M.; Yakovlev, V.A.
Abstract: Carbon–silica nanocomposites obtained by rice husk carbonization in a fluidized-bed reactor using a deep oxidation copper–chromium catalyst were studied. Dispersion characteristics of the silica phase in these systems were determined by small-angle X-ray scattering (SAXS) using the full contrast technique. SiO2 was found in the initial rice husk as compact nanoparticles having a wide size distribution. This distribution consists of a narrow fraction with particle sizes from 1 to 7 nm and a wider fraction with particle sizes from 8 to 22 nm. Oxidative heat treatment of rice husk in a fluidized bed in the presence of the catalyst decreased the fraction of small SiO2 particles and increased the fraction of large ones. It was demonstrated that the particle size of silica in the carbon matrix can be determined selectively for deliberate design of porous carbon materials with desired properties. Graphical abstract: Highlights: It has been found that silicon from rice husk present as form silica nanoparticles. Silica particle size distributions have been determined in amorphous carbon–silica composites based on the new technique for SAXS analysis. Increasing the heat treatment temperature to 600 °C for preparation composites from rice husk increases the average particle size of the silica phase from 4.7 to 7.6 nm.